HABITUS RELIGIUS SISWA MELALUI PROGRAM SEKOLAH RAMAH ANAK DI MADRASAH IBTIDAIYAH - Alfi Ibnu Rusy; Muh. Hanif Muh. Hanif (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study discusses the formation of students' religious habitus through the Child-Friendly School Program at MI Ma'arif NU Banjaranyar. This issue is important because religious habituation in madrasah is often understood merely as a routine activity, whereas it also contains social relations, rules, exemplary behavior, a sense of safety, and the way the institution treats children as educational subjects. This research used a qualitative approach with a case study design. Data were obtained through field observations, interviews with the head of madrasah, teachers, and students, as well as documentation in the form of the madrasah profile, religious programs, and anti-bullying program reports. The data were analyzed thematically by focusing on three concepts: religious habitus, child-friendly school, and cultural, social, and symbolic capital. The results show that the Child-Friendly School Program functions as a structure that provides a safe space for forming religious habits. Activities such as prayers before learning, memorization of Asmaul Husna, memorization of Juz 30, Dhuha prayer, tahlil, istighasah, and congregational Zuhur prayer are not separate agendas, but are integrated into a madrasah atmosphere that rejects violence and prioritizes close teacher-student relationships. Teachers act as agents who translate Islamic values into daily practices, while the head of madrasah and institutional programs provide legitimacy so that habituation remains consistent. The findings affirm that students' religious habitus grows not merely through advice, but through repeated practices that are socially accepted and feel safe for children.